Penegakan Hukum Terhadap Eksistensi Jasa Joki Tugas Akhir Mahasiswa Perspektif Tanggun Jawab Hukum - Putra, Aldi; Perdana, Albar (Ilmu Hukum Prima (IHP), 2024)
Jockey services in higher education used by students are a form of ethical violation and are subject to sanctions. The legal umbrella of the prohibition of jockey services is regulated in Article 15 paragraph (2) of the Law on the National Education System, Article 18 to Article 20 of the Regulation of the Minister of Education, Culture Research and Technology on Quality Assurance of Higher Education, Article 72 of the Law on Copyright and several regulations made by universities. However, jockeying services are often equated with the term plagiarism, which, of course, has a different meaning, so law enforcement against the handling of jockeying services is still unclear. This research uses normative research. The nature of the research is descriptive qualitative. Data collection methods using literature study. Legal materials consist of primary legal materials, secondary legal materials, and tertiary legal materials. The analysis used is a qualitative method. The need for law enforcement in final assignment jockey services is essential because every related legal product still terms jockey services, including plagiarism, which actually has a difference. In addition, universities certainly have strict regulations and oppose the act of cheating in the university environment. Regulations regarding jockey services in universities are the first milestone in regulating the use of jockey services.